2010
DOI: 10.2463/mrms.9.101
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Magnetic Resonance Imaging Dealing with Low Temperature Objects

Abstract: In Japan, the medical examiner system is not widespread, the rate of autopsy is low, and many medical institutions therefore perform postmortem imaging using clinical equipment. Postmortem imaging is performed to clarify cause of death, select candidates for autopsy, make a guide map for autopsy, or provide additional information for autopsy. Findings are classiˆed into 3 categories: cause of death and associated changes, changes induced by cardiopulmonary resuscitation, and postmortem changes. Postmortem magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Therefore, PMMR imaging shows changes in SI in response to lowering body temperature after death. [12][13][14] It is difficult to achieve a consensus on the normal appearance of PMMR because these changes depend on temperature. Therefore, PMMR parameter optimization is needed to obtain appropriate image contrast for bodies at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, PMMR imaging shows changes in SI in response to lowering body temperature after death. [12][13][14] It is difficult to achieve a consensus on the normal appearance of PMMR because these changes depend on temperature. Therefore, PMMR parameter optimization is needed to obtain appropriate image contrast for bodies at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…15 However, routine parameters for MR imaging of the living body do not suppress the SI of cerebrospinal fluid (CSF) of cadavers. 12,13,16 Tofts and associates reported that T 1 values of the CSF can be derived by measuring the diffusion coefficient of the CSF at low temperatures. CSF signals of the cadaveric brain can then be suppressed effectively by using an optimized inversion time (TI).…”
Section: Introductionmentioning
confidence: 99%
“…21 Application of the inversion time (TI) for living bodies for PMMR imaging does not adequately suppress fat signals in STIR and CSF signals in FLAIR. [18][19][20] Suppression of the signal intensity (SI) of fat has been reported with STIR in PMMR imaging when using an optimized TI based on the measured rectal temperature (RT). 22 Therefore, we surmised that the SI of CSF can also be suppressed on postmortem FLAIR images by adjusting the TI according to the T 1 temperature dependence of water.…”
Section: Introductionmentioning
confidence: 99%
“…However, consensus regarding what constitutes a normal appearance on PMMR images is difficult because T 1 and T 2 values change according to body temperature. 12,[18][19][20] Therefore, acquisition of appropriate image contrast for deceased bodies at low temperatures re-*Corresponding author, Phone: +81-92-554-1255, Fax: +81-92-552-2707, E-mail: abe.k@junshin-u.ac.jp quires optimization of the parameters for PMMR imaging. Short-tau inversion recovery (STIR) and fluidattenuated inversion recovery (FLAIR) are typical sequences employed to suppress tissue signal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation